Research on the Path of Carbon Market Risk Governance Empowered by Accounting Tools - Xinyao Zhang (Asia Pacific Economic and Management Review, 2026)
Based on the background of the implementation of China’s "Dual Carbon" strategy and closely focusing on the practical needs of carbon market risk governance, this paper systematically explores the internal logic and practical paths of accounting tools empowering carbon market risk governance. The research first conducts risk identification and measurement analysis, and then clarifies the characteristics and impacts of four types of core risks in the carbon market: (1) Market manipulation and price fluctuation risks impact the market pricing mechanism and the financial stability of enterprises; (2) Data quality and integrity risks weaken the credibility of transactions and lead to regulatory failure; (3) Policy arbitrage and carbon leakage risks damage market fairness and hinder the achievement of emission reduction targets; (4) Quota allocation and market imbalance risks result in resource misallocation and inhibit market liquidity. On this basis, a multi-dimensional risk governance path system of accounting tools is constructed: fair value measurement, hedge accounting and other tools are used to stabilize price fluctuations; carbon accounting information systems and audit supervision are relied on to strengthen credit risk management; policy tracking and accounting adaptation are adopted to respond to policy change risks; risk transfer and sharing mechanisms are established by means of risk reserve accrual and carbon financial tool innovation. This research clarifies the core functions and application value of accounting tools in carbon market risk governance, provides theoretical support and practical reference for improving the carbon market risk governance mechanism and enhancing market operation efficiency, and helps the carbon market better play its role in resource allocation in the low-carbon transformation.